2022
DOI: 10.21203/rs.3.rs-2234040/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of a postpartum care rehabilitation program to prevent postpartum depression at a Secondary Municipal Hospital in Qingdao China: a cross-sectional study

Abstract: Background The emerging postpartum rehabilitation (PPR) program in Chinese hospitals characterized by applying ongoing medical care through traditional cultural practices shows a protective effect in early puerperium in China. This study explores the benefit of PPR program practices to postpartum depression (PPD) and other possible influencing factors for PPD among Chinese women during the first postnatal six weeks. Methods The cross-sectional study included 403 participants and was conducted in a Secondary… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previous research has already demonstrated the effectiveness of intensive postpartum rehabilitation programs. 56 As noted above, while the reported pooled effect sizes in this umbrella review may be considered small from a statistical perspective, such a narrow view underestimates the true clinical importance of our findings. 30 A more appropriate assessment involves interpreting PAFs.…”
Section: Discussionmentioning
confidence: 76%
“…Previous research has already demonstrated the effectiveness of intensive postpartum rehabilitation programs. 56 As noted above, while the reported pooled effect sizes in this umbrella review may be considered small from a statistical perspective, such a narrow view underestimates the true clinical importance of our findings. 30 A more appropriate assessment involves interpreting PAFs.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, learning health care knowledge about pregnancy and neonatal care skills during pregnancy is advantageous for primiparas to have more E after delivery and to take better care of their newborns, thereby decreasing the likelihood of postpartum depression. [19]…”
Section: Discussionmentioning
confidence: 99%